Experimental Testing and Numerical Modeling of Robust Unreinforced and Reinforced Clay Masonry Infill Walls, With and Without Openings - da Porto, Francesca; Donà, Marco; Verlato, Nicolò; Guidi, Giovanni (Frontiers in Built Environment, 2020)
This paper presents an overview of the experimental results obtained by combined in-plane/out-of-plane (IP/OOP) tests carried out on robust clay masonry infill walls. The combined tests were carried out on eight full-scale one-bay, one-storey infilled RC frames, plus one reference RC bare frame. In four cases, the masonry walls fully fill the RC frame: two walls are made of unreinforced masonry (URM), whereas other two are made of reinforced masonry (RM), with both vertical and horizontal reinforcement. Each pair of specimens was tested up to different levels of IP drift, before carrying out the OOP tests. Other four specimens, still made of URM and RM walls, are characterized by the presence of a central opening, and in one case, the effect of a lintel is analysed. On the basis of the tests carried out, an analytical model was developed for the analysis of the OOP behaviour. It was used to calibrate IP damage degradation models based on the experimental results, to define limits for the applicability of well-known flexural and arching mechanism models for the evaluation of the OOP capacity of the infill walls, and to evaluate the efficiency of vertical reinforcement. In this work, the experimental campaign is presented and the results of both experimental tests and numerical analyses are discussed.